KARAKTERISTIK KEPEMIMPINAN PENDIDIKAN BERBASIS ISLAM DI ERA DIGITAL - Irwan Rusniawan; Ihdi Fuadi; Irnie Victorynie (STKIP Subang, 2025)
The purpose of this article is to determine the characteristics of Islamic-based educational leadership that are relevant to the development of the era, namely the industrial revolution era marked by the massive use of digital technology in almost all lines of life, especially the world of education. This writing uses a library research method with a descriptive exploratory literature approach, namely by conducting an in-depth study and collecting data on the characteristics of Islamic-based educational leadership and the phenomenon of the digital era through relevant books, journals, scientific articles, interviews and the internet. The characteristics of an ideal Islamic-based educational leader in this digital era include: having intrinsic prophetic characteristics, namely shiddiq, amanah, tabligh, fathanah, qana'ah, and syaja'ah, having the ability to see opportunities, being a pioneer and motivator in designing and implementing digital-based education, being able to mobilize all elements of existing human resources, having a corporate mindset, having a good driver mentality, and always being open-minded and welcoming to changes that continue to move rapidly without hesitating to try new things related to digital technology.